Psychological Trauma Recovery After Flooding in Sibolga: A Clinical Approach Based on Community Local Wisdom - Meri Susanti; Ira Aini Dania (Media of Health Research, 2026)
Flood disasters can cause prolonged psychological distress, particularly when formal mental health interventions are culturally disconnected from affected communities. This study examines psychological trauma recovery among flood survivors in Sibolga, North Sumatra, by integrating clinical approaches with community local wisdom. An explanatory sequential mixed-method design was employed. Quantitative data were collected from 150 adult flood survivors selected through purposive sampling using questionnaires measuring motivation, perception, attitude, and interest in trauma recovery. Qualitative data were obtained through semi-structured interviews, field observations, and discussions with survivors, religious figures, and community leaders. Quantitative data were analyzed using descriptive statistics and hypothesis testing, while qualitative data were examined through thematic analysis. The results showed that motivation significantly influenced survivors' attitudes and interest in trauma recovery but did not significantly influence their perceptions of formal psychological services. Qualitative findings identified collective meaning-making, spiritual practices, cooperation, family support, and trust in local leaders as important recovery mechanisms. These findings indicate that culturally embedded practices can strengthen emotional regulation, community participation, and acceptance of psychological interventions. The study proposes an indigenous clinical recovery model combining professional psychological support with culturally legitimate community practices.